Minimal-invasive versus open hepatectomy for hepatocellular carcinoma: Comparison of postoperative outcomes and long-term survivals using propensity score matching analysis. (December 2018) - Andreou, Andreas; Struecker, Benjamin; Raschzok, Nathanael; Krenzien, Felix; Haber, Philipp; Wabitsch, Simon; Waldbaur, Christoph; Touet, Eva-Maria; Eichelberg, Anne-Christine; Atanasov, Georgi; Biebl, Matthias; Bahra, Marcus; et al.
Abstract: Background: Minimal-invasive hepatectomy (MIH) has been increasingly performed for benign and malignant liver lesions with most promising results. However, the role of MIH for the treatment of patients with hepatocellular carcinoma (HCC) needs further investigation. Methods: Clinicopathological data of patients who underwent liver resection for HCC between 2005 and 2016 were assessed. Postoperative outcomes und long-term survivals of patients following MIH were compared with those of patients undergoing conventional open hepatectomy (OH) after 1:1 propensity score matching. Results: During the study period, 407 patients underwent liver resection for HCC with curative intent. Fifty-six patients underwent MIH and were compared with a matched cohort of 56 patients who underwent OH. The rate of patients with fibrosis/cirrhosis (82% vs. 86%, p = 0.959), multiple lesions (32% vs. 32%, p = 1.00), tumor size >30 mm (61% vs. 55%, p = 0.566), and major resection (16% vs. 16%, p = 1.00) was comparable between the two groups (MIH vs. OH). MIH was associated with lower 90-day complication rate (32% vs. 54%, p = 0.022), lower postoperative major complication rate (14% vs. 30%, p = 0.041), lower liver failure rate (0% vs. 7%, p = 0.042), lower 90-day mortality rate (0 vs. 7%, p = 0.042), and shorter length of hospital stay (9 vs. 12 days, p = 0.009) compared to OH. After a median follow-up time of 51 months, MIH and OH showed comparable 5-year overall survival (54% vs. 41%, p = 0.151), and 5-year disease-free survival rates (50% vs. 38%, p = 0.956). Conclusions: MIH for HCC is associated with lower postoperative morbidity and mortality and shorter length of hospital stay, resulting in oncologic outcomes similar to those achieved with the established OH. Our findings suggest that MIH should be considered as the preferred method for the treatment of curatively resectable HCC. Highlights: MIH was associated with significantly lower morbidity, mortality, and shorter length of hospital stay compared to OH. MIH resulted in oncologic outcomes similar to those achieved by the established OH. MIH should be considered as the preferred method for the treatment of curatively resectable HCC.